POTENCIAL FISIOLÓGICO E DO RENDIMENTO DE GRÃOS EM CULTIVARES DE AVEIA BRANCA RECOMENDADAS PARA O SUL DO BRASIL - Matter, Edegar; Antonow, Diovane; Bandeira, Taiane P.; Oliveira, Juliana M. d.; Silva, Adair J. d.; Vieira, Rogério; Mattioni, Tânia C.; Fontaniva, Cristiano; Silva, José A. G. d.; Berto, Jorge L. (Salão do Conhecimento, 2013)
Resumo